Sur les fractions lipidiques de Mya arenaria l. - Molnar, A.; Mîrza, Maria; Panteli, C. (Cercetări Marine - Recherches Marines, 2026)
There had been determined the content and composition of free bound and total lipids from Mya arenaria in glycerides, phospholipids, unsaponifiable. It was shown that the phospholipids had a great capacity to form cenapses than the other components. It was discussed that the fraction of bound lipids was richer in lecithin and lysolecithins and poorer in cephalins and lysocephalins than the free one.